Body weight measurements relationship in Nigerian Red Sokoto goats - Hassan, A.; Ciroma, A. (1992)
Bodyweight and linear body measurements (body length, height-at-withers and heart girth) of 201 male and female goats in three age groups (1-2, 3-4, 5 years and above) averaged 16.41, 22.94, 30.02 kg; 79.15, 87.33, 96.57 cm; 57.49, 62. 77, 67.39 cm; 61. 78, 67.86 and 75.77 cm, respectively.The coefficients of variation (CVS) were 23.0, 17.3, 16.8; 6.9, 6.1, 5.8: 8.4, 4.6, 5.8; 11.2, 6.2, 6.9%. Males were heavier (P<0.05) and longer (P<0.01) than females at 3-4 years of age. Females stood higher (P<0.01) at withers at 1-2 years of age but were shorter than the males (P <0.001) at 3-4 years of age. The heart girth of the males was bigger than those of females at 3-4 years (P<0.01) and also 5 years (P < 0.05). Significantly (P < 0. 05) affected by sex at 3-4 years; sex effect was also highly significant (P<0.01) on body length at the same age. Height at withers differed significantly between males and females at 1-2 years (P<0.05) and 3-4 years (P<0.001). Significant sex effect was also observed on hears girth at 3-4 years (P<0.01) and 5 years and above (P<0.05). Bodyweight was correlated with body length (0.45, 0.53, 0.75), height-at-withers (0.73, 0.47, 0.55) and heart girth (0.78, 0.38, 0.58).Based on the magnitude of the correlation coefficients, body length and height-at-withers could be used for predicting liveweight of the animals at 1-2 years and 3 years and above, respectively.